MANAJEMEN PRODUKSI PROGRAM BELACAN DI RIAU TELEVISI DALAM MEMPERTAHANKAN MUSIK DAERAH DI PEKANBARU - Rapih Hasnan; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is motivated by the researcher’s interest in world television. Currently the television Indonesia. This time televisioon is a very popular media of indonesian people, includng the Peknbaru area. Besides the researchers are also intersted in discussing cultural resilience in Pekanbaru area of impact the globalization that adversely affect the culture in a country. For that reserchers do reserch in order to see the program belacan in Riau Television by looking at the management angle of television production because the balacan programs is a program that display regional cultural music..This purpose uses quality methods. Data retrieval using interview techniques, observation teqhniques, dokumentary teqhniques and using the POAC theory for looking of planning, organizing, actuating and supervision of the management. The purpose of this study is to find out how the plaanning, organizing, actuating and supervision of the production management the balacan program in Riau Telvision in maintaining regional music in Pekanbaru area. The result of research on the production of the balacan program in Riau Television in maintaining regional music in Pekanbaru area of effective saids to maintaining resilience and perseve regional music in Pekanbaru in the current era  of globalization. Sen from the planning  of the balacan program on displayed of the music regional as many six the regional music to adjus to the peolple who live in Pekanbaru of the multiculture people. Orgnizing of this the balacan program are compiled and have credibility that fits the position in production. Actuatng the belacan program in guided by the host who uses language and fashion is thick wit regional culture. And the supervision of the belacan program carried out was very instrumental in overseeing the production of the belacan program.   Keywords: Production television management, Terry (POAC), Planning, Organizing, Actuating and Coontrolling.